LESI ULSERASI RONGGA MULUT YANG SERING DIJUMPAI BERHUBUNGAN DENGAN INFEKSI VIRUS - Siti Aliyah Pradono (Faculty of Dentistry, Universitas Indonesia, 2015)
The oral mucosa is the target of a number of infectious processes caused by a range of organism. Viruses is one of the organism which is considered in oral mucosal damage. Recently, the main viruses causing oral mucosal infections are the large herpes group. This article discuss herpes simplex virus and varicella zoster virus that cause herpetic stomatitis and herpes zoster, with particular attention to the typical oral manifestations, current treatmetn options. Dentists should recognize the clinical appearances of the diseases, so the appropriate therapy can be done.